2019
DOI: 10.1002/anie.201902864
|View full text |Cite
|
Sign up to set email alerts
|

Globular Polymer Grafts Require a Critical Size for Efficient Molecular Sieving of Enzyme Substrates

Abstract: A series of 2,2‐bis(hydroxymethyl)propionic acid dendrons of generation 2 through 8 having a strained cyclooctyne at the core and hydroxy groups at the periphery were prepared by a divergent method and used to functionalize azide‐decorated α‐chymotrypsin. The ability of the appended dendrons to selectively block enzyme activity (through a molecular sieving effect) was investigated using a small molecule substrate (benzoyl‐l‐tyrosine p‐nitroanilide), as well as two proteins of different size (casein and bovine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Ligand binding rate depended strongly on the ligand size and grafting density, but not on ligand shape or polymer chain length. In another example, Adronov et al reported CT-polyester dendrimer conjugates with increasing numbers of generations finding that 7 generations were needed for effective sieving . Grafted-from protein–polymer conjugates have not yet been FDA-approved.…”
Section: Protein–polymer Conjugatesmentioning
confidence: 99%
“…Ligand binding rate depended strongly on the ligand size and grafting density, but not on ligand shape or polymer chain length. In another example, Adronov et al reported CT-polyester dendrimer conjugates with increasing numbers of generations finding that 7 generations were needed for effective sieving . Grafted-from protein–polymer conjugates have not yet been FDA-approved.…”
Section: Protein–polymer Conjugatesmentioning
confidence: 99%
“…It is worth noting that the R g for aprotinin is only 1.1 nm. While it has been demonstrated that increasing polymer grafting density or attachment of several generation dendrimers can reduce permeation of smaller molecules (casein) and hinder permeation of larger molecules (BSA), , the data provided herein provide the first evidence, to our knowledge, that rationally designed nanoarmored protein–polymer conjugates can prevent protein–protein interactions while preserving biological activity.…”
Section: Discussionmentioning
confidence: 72%
“…Having prepared the PEGylated dendrons with reactive DBCO units at the core, we proceeded to graft these structures to the surface of α-CT, following previously established protocols . Treatment of the 14 surface lysine residues of α-CT with 2-azidoacetic acid introduced the required azide functionalities on the enzyme to allow SPAAC coupling with the dendrons while maintaining aqueous solubility.…”
Section: Resultsmentioning
confidence: 99%
“…The above work infers that optimizing sieving activity on a protein conjugate is a multifaceted process that cannot simply be achieved through modifying grafting density, architecture, or molecular weight alone. Using a different approach, our group has recently explored molecular sieving in dendritic polymer conjugates, specifically high-generation dendrimer-chymotrypsin (CT) hybrids . Dendrimers offer excellent control over dispersity and morphology, which we rationalized would ensure a uniform monolayer when grafted onto the enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation